1995
DOI: 10.1111/j.1399-0039.1995.tb02450.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA—DPB1 alleles in a population from North India and description of a new variant (DPBl*5601)

Abstract: : HLA‐DPB1 alleles were studied in 51 normal individuals and 93 leprosy patients from North India using a PCR‐oligotyping technique. Hybridization patterns could identify 47 alleles of which 20 were found in the population studied. DPB1*0401 was found to be the most frequent allele with a frequency of 66.7% followed by DPB1*0402 (21.6%), DPB1*0201 (21.6%), DPB1*1301 (15.7%) and DPB1*0301 (13.7%). Besides the common alleles, DPB1*0101, *1701, *2601, *1001, *1601, *0901, *2901, *1501, *0501, *1401, and *3301 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
1
4
1
Order By: Relevance
“…While we observed a very low frequency of 1858T allele in North Indians [25], earlier studies reported a total absence of T allele in Asian populations [23]. Our study suggests that Asian populations cannot be generalized as one ethnic group since the earlier reports of absence of the T allele have been from Asian populations from Japan, Korea and China, which being Mongoloid in origin, are ethnically different from Indians who are basically Caucasoid with racial admixture of Mongoloid and Negroid elements [45].…”
Section: Discussioncontrasting
confidence: 74%
“…While we observed a very low frequency of 1858T allele in North Indians [25], earlier studies reported a total absence of T allele in Asian populations [23]. Our study suggests that Asian populations cannot be generalized as one ethnic group since the earlier reports of absence of the T allele have been from Asian populations from Japan, Korea and China, which being Mongoloid in origin, are ethnically different from Indians who are basically Caucasoid with racial admixture of Mongoloid and Negroid elements [45].…”
Section: Discussioncontrasting
confidence: 74%
“…B*4006 is commonly seen among South Koreans, Chinese, Koreans and Japanese (2, 4). This reinforces the fact that Asian Indians are basically Caucasoid with mongoloid (oriental) and black admixture (5). The novel allele described in the index study seems to be a hybrid sharing sequences with B*4006 and B*0702.…”
supporting
confidence: 77%
“…It is found to be frequently associated with A*0211 in Asian Indians. The frequency of haplotype HLA‐A*0211‐B*4006 in the Asian Indian population is reported as 6.86% and that of A*02–B*40 is 11.76% (5). B*4006 is commonly seen among South Koreans, Chinese, Koreans and Japanese (2, 4).…”
mentioning
confidence: 99%
“…We have earlier shown the presence of frequent Black and Chinese alleles and haplotypes in North Indians (Rani et al ., 1995, 1998a). In the present study, we also found the presence of alleles that are prevalent in Blacks like A*6801, B*5301, B*44032, B*4006 and Cw*1701, and also those that are found in Orientals like B*1301, B*1502 and B*4006 (Fernandez‐Vina et al ., 1995; Hsu et al ., 1995), thus confirming the fact that Indians are basically Caucasoid with Mongoloid and Black admixture, and thus confirming our earlier observations using class‐II alleles (Rani et al ., 1995, 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…For a complete description of the system and because of their potential role in bone marrow transplantation and manifestations of certain diseases, we have re‐investigated the frequencies of the HLA class‐I alleles in North Indians. Earlier we have reported frequencies of HLA class‐II alleles and their associations in this population (Rani et al ., 1995, 1998a) and their frequencies remain similar even when the population size has now been increased, hence here we have concentrated on the frequencies of HLA class‐I alleles only in this population.…”
Section: Introductionmentioning
confidence: 99%